Implementation of sensor-based control algorithms in an industrial robot controller - Carozzi, C.; Magnani, G.; Nicolodi, S. (Control engineering practice, 1995)
This paper presents a prototype robot controller that allows easy implementation of model-based andsensor-based control concepts. The prototype is built around the state-of-the-art industrial COMAU C3G controller and it accomodates the additional control functions by integrating additional hardware and software modules in the standard controller architecture. Therefore this seems a promising approach for the introduction of sensor-based control in industrial robotics. The prototype proves to be interesting for robotics research also, since it combines flexibility with the reliability of standard industrial components.